Key achievements in gene therapy development and its promising progress with gene editing tools (ZFN, TALEN, CRISPR/Cas9) - Franić, Dina (Array, 2019)
Gene therapy concept is based on introduction of the wild-type allele into a patient’s genome in order to reverse a specific mutation. It is designed to treat hereditary diseases as well as the other diseases occurring later in life. Gene therapy was first mentioned in the 1960s and 70s, whereupon a series of studies was carried out, and in 1990 the first successful gene therapy was conducted. Since then about 2 600 clinical trials based on this concept were completed or are in progress. The two biggest issues are introduction of an exogenous DNA to target tissue, and its controlled integration in the genome. Until recently, the exogenous DNA sequences were incorporated randomly in the patient’s genome. Even though most of these treatments gave positive results, there was always a possibility of insertional mutagenesis. Controlling the integration place has rapidly progressed with the development of gene editing tools: ZFN, TALEN and CRISPR/Cas9. Although they have been used in only several clinical studies, gene editing tools are a small step away from clinical usage. In this review, we will give historical overview of gene therapy development and describe recent tools that can be used in precision medicine.